Octopus visual system: A functional MRI model for detecting neuronal electric currents without a blood‐oxygen‐level‐dependent confound. Issue 5 (2nd December 2013) - Jiang, Xia; Lu, Hanbing; Shigeno, Shuichi; Tan, Li‐Hai; Yang, Yihong; Ragsdale, Clifton W.; Gao, Jia‐Hong
<x xml:space="preserve">Abstract</x> Purpose Despite the efforts that have been devoted to detecting the transient magnetic fields generated by neuronal firing, the conclusion that a functionally relevant signal can be measured with MRI is still controversial. For human studies of neuronal current MRI (nc‐MRI), the blood‐oxygen‐level‐dependent (BOLD) effect remains an irresolvable confound. For tissue studies where hemoglobin is removed, natural sensory stimulation is not possible. This study investigates the feasibility of detecting a physiologically induced nc‐MRI signal in vivo in a BOLD‐free environment. Methods The cephalopod mollusc Octopus bimaculoides has vertebrate‐like eyes, large optic lobes (OLs), and blood that does not contain hemoglobin. Visually evoked potentials were measured in the octopus retina and OL by electroretinogram and local field potential. nc‐MRI scans were conducted at 9.4 Tesla to capture these activities. Results Electrophysiological recording detected strong responses in the retina and OL in vivo; however, nc‐MRI failed to demonstrate any statistically significant signal change with a detection threshold of 0.2° for phase and 0.2% for magnitude. Experiments in a dissected eye‐OL preparation yielded similar results. Conclusion These findings in a large hemoglobin‐free nervous system suggest that sensory evoked neuronal magnetic fields are too weak for direct detection with current MRI technology. Magn Reson Med 72:1311–1319, 2014. © 2013 Wiley Periodicals, Inc.